Suitability Analysis and Carrying Capacity of Marine Ecotourism Based on Swimming, Fishing, and Boating Activities at Marsegu Island, Kotania Bay - Bambang Sondi; Masudin Sangaji; Niette V. Huliselan (International Journal of Science and Environment (IJSE), 2026)
Marsegu Island in Kotania Bay, West Seram Regency, Maluku Province, holds remarkable ecological potential that is worth developing as a sustainable marine ecotourism destination. This study aims to analyze land suitability and carrying capacity and formulate development strategies for marine ecotourism activities covering swimming, fishing, and boating. Data were collected during August–September 2024 through biophysical parameter measurements at three observation stations, supplemented by interviews, questionnaires, and field observations. Tourism suitability was calculated using the Tourism Suitability Index (TSI), carrying capacity using the Carrying Capacity (CC) formula, and strategy prioritization using descriptive integrated analysis. Results indicate that fishing and boating tourism at all three stations fall under category S1 (highly suitable), while swimming tourism at two stations is classified as S1 and one station as S2 (suitable). Carrying capacity ranges from 21–59 visitors/day for swimming, 100–120 visitors/day for fishing, and 144–160 boat units/day for boating tourism. The results of this study recommend that the zoning system be implemented as a policy strategy for the development of marine ecotourism on Marsegu Island, with 4 zoning directions and 6 policy recommendations. Integrated management based on carrying capacity principles and zoning systems is fundamental to ensuring the long-term sustainability of ecotourism in this area.